Review Article about Medical Devices Used in Gallstone Lithotripsy: Types and Applications - abd jabar, Ruqaya Haider; salman Farhan, Rusul dawood; Othman Faleh, Najla Khader; rahi jaber, Tabark abd Alhussin; Kben jbr, Noor Alhuda Waheed; Dhayool Qasim, Yaqeen Sameer (American Journal of Botany and Bioengineering, 2025)
Lithotripsy techniques are very important because of their non-invasive nature. There have been many clinical practices with this technology in recent years. The aim of this review is to create a knowledge base for various medical devices used in gallstone lithotripsy and to shed light on the effectiveness of these devices in clinical practice. In this review, extracorporeal, endoscopic, and per-oral transepatic approaches are going to be examined in a comparative manner. Medical devices used in these lithotripsy techniques, as well as their working principles and areas of application, are going to be detailed. There are three main types of lithotripsy devices; shockwave, laser and mechanical. The lithotripsy devices used to break the stones in small pieces are called lithotripters in general. Lithotripters can be classified as extracorporeal, contact and mechanical lithotripters. Extracorporeal lithotripters generate mechanical shock waves, mechanically degrade the stone by the application of an externally applied force. The stone or the organ containing the calculus is outside of the body in this technique. Endourology combines endoscopic and imaging technology. ESWL and percutaneous nephrolithotomy (PNL) are frequently used in the application of this technique. Mechanical lithotripsy is applied through orundum and metal baskets, and is frequently used in bile duct and pancreatic lithotripsy applications . There are a number of commercial products available in gallstone lithotripsy. ESWL has been safely and effectively used in management of urolithiasis in developed countries. And so far, it has been possible to get access to ESWL technology for only private practice in developing countries. However, it has been possible to receive this service through new practices as well. In this practice an electro hydraulic generator incorporating the cavitation principle was used. With the effect of the shock wave, the size of the stones gets reduced and the stone parts are expulsed either in the urine or spontaneously.